BMI1 fine-tunes gene repression and activation to safeguard undifferentiated spermatogonia fate - Liu, Ruiqi; Peng, Yonglin; Du, Wenfei; Wu, Yunqiang; Zhang, Wen; Hu, Congxia; Liu, Min; Liu, Xinhua; Wu, Ji; Sun, Jielin; Zhao, Xiaodong (Frontiers in Cell and Developmental Biology, 2023)
Spermatogenesis is sustained by the homeostasis of self-renewal and differentiation of undifferentiated spermatogonia throughout life, which is regulated by transcriptional and posttranscriptional mechanisms. B cell-specific Moloney murine leukemia virus integration site 1 (BMI1), one of spermatogonial stem cell markers, is a member of Polycomb repressive complex 1 (PRC1) and important to spermatogenesis. However, the mechanistic underpinnings of how BMI1 regulates spermatogonia fate remain elusive. Here, we demonstrate that BMI1 is required for undifferentiated spermatogonia maintenance by both repressing and activating target genes. BMI1 preserves PI3K-Akt signaling pathway for spermatogonia proliferation. Decrease of BMI1 affects the deposition of repressive histone modifications H2AK119ub1 and H3K27me3. BMI also positively regulates H3K27ac deposited genes which are associated with proliferation. Moreover, we demonstrate that BMI1 interacts with Sal-like 4 (SALL4), the transcription factor critical for spermatogonia function, to co-regulate gene expression. Overall, our study reveals that BMI1 safeguards undifferentiated spermatogonia fate through multi-functional roles in regulating gene expression programs of undifferentiated spermatogonia.